Career Planning of SMA Cibitung Bekasi District Students - Nurmawati Nurmawati; Nilla Fauziah (Syntax Literate, 2022)
Objective – This research was conducted to know the high and low career planning of high school students in Cibitung District, Bekasi Regency, who will carry out Career Planning for the future to be brighter. Design/Methodology/Research – The research was conducted on SMA Negeri Class XI Science students in Cibitung District, Bekasi Regency, including SMA Negeri 1 Cibitung and SMA Negeri 2 Cibitung. This research was conducted from November 2021 – to April 2022 with quantitative research using a descriptive approach. The sample collection used was simple random sampling with a total sample of 170 students. Instruments - Types of instruments used are questionnaires or questionnaires with a Likert scale in the form of scoring intervals of 1-4, which will be carried out in data analysis using SPSS 23. Results and Conclusions The level of career planning for high school students in Class XI Science in Cibitung District, Bekasi Regency. Most of them are in the high category with a percentage of 91.20% or 155 students, then followed by the low category with a percentage of 6.50% or 11 students, then followed by a very high category with a percentage of 2.40% or four students, and a very low category with a percentage of 0% or 0 students. The level of career planning for high school students in Class XI Science in Cibitung District, Bekasi Regency, is based on self-assessment factors, exploring opportunities, making decisions and goal setting, planning, and pursuit of achievement.